2021
DOI: 10.1002/ams2.639
|View full text |Cite
|
Sign up to set email alerts
|

Successful covered stent‐graft treatment of superficial femoral arterial injury due to blunt trauma

Abstract: Background Endovascular treatment is used for traumatic arterial injuries in the torso. However, the effectiveness of endovascular covered stent‐graft treatment for peripheral artery injury is unclear. We present a case of superficial femoral artery (SFA) injury successfully treated with a covered stent‐graft. Case Report A 68‐year‐old man presented with traumatic lower limb injury and shock. Computed tomography angiography revealed left subtrochanteric fracture and hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Dual antiplatelet therapy is recommended after treatment of non-traumatic peripheral arterial occlusion or stenosis with stent graft. However, optimal antiplatelet therapy in patients with active bleeding treated by using stent graft is not clear [13]. In a meta-analysis, it was reported that in all studies it was recommended that patients should use at least one antiplatelet agent, ranging durations from 3 months to lifelong [14].…”
Section: Discussionmentioning
confidence: 99%
“…Dual antiplatelet therapy is recommended after treatment of non-traumatic peripheral arterial occlusion or stenosis with stent graft. However, optimal antiplatelet therapy in patients with active bleeding treated by using stent graft is not clear [13]. In a meta-analysis, it was reported that in all studies it was recommended that patients should use at least one antiplatelet agent, ranging durations from 3 months to lifelong [14].…”
Section: Discussionmentioning
confidence: 99%